Administration Of Moringa Leaf Meatballs to Prevent Stunting in Toddlers - Rukmaini; Nova Iswanda S; Islamagesvi, Anggie; Eneng Kurnia Dewi; Mery Merdiani; Santi Damayanti; Sri Ati Rahmawati; Wanti Warsiti (Rajaki of Tulip Medika Publisher, 2025)
The problem of malnutrition in Indonesia can have a serious impact on the decline in the quality of Human Resources (HR). One of the problems of malnutrition is the high number of cases of stunting children under five, stunting can be said to be toddlers who experience chronic nutrition due to low nutritional intake, and the lack of knowledge of housewives in meeting the availability of nutrition in the family. This community service activity aims to provide education through health promotion to parents of PAUD children about stimulating healthy menu choices for PAUD children in preventing stunting. This activity was carried out at PAUD Melati in West Bandung, involving children, parents, and school stakeholders. Starting with the introduction of food ingredients, demonstration of making Moringa Leaf Pentol, education about nutrition to parents. The results of the activity showed that during the implementation, children showed high interest in making Moringa Leaf Pentol, especially when they saw interesting shapes and colors. Parents were also seen actively participating in the activities and giving full attention to the nutrition education provided.